Esports: an exploration of the advancing esports landscape, actors and interorganisational relationships - Wong, Donna; Meng-Lewis, Yue (Sport in Society, 2023)
Evolving along with technological advancement and representing a complex digital phenomenon, esports is a rising nascent industry with knowledge gaps on how the current esports landscape and key actors operate. The esports ecosystem is characterised by the confluence of multiple interrelated leisure industries of sports, media, and entertainment. The overall esports operation could be elucidated only through mapping out critical actors, their roles and interrelationships. Using the framework of the Interorganisational Relations Theory (IOR), we present the contemporary esports landscape by exploring its production, distribution and consumption processes. Through examining the key actors of the esports value chain and their interorganisational relationships, we analysed how the esports industry is developed, supported and sustained through their collaborative efforts. This study contributes to evidence-based theorising of the esports industry, which is necessary to reflect on the current setup and infrastructure needed for the industry's sustainable development.